2001
DOI: 10.1046/j.0014-2956.2001.02527.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antifeedant activity in brain extracts led to the identification of sulfakinin as a satiety promoter in the German cockroach.

Abstract: The feeding cycle of the adult female cockroach Blattella germanica parallels vitellogenesis. The study of the mechanisms that regulate this cycle led us to look for food-intake inhibitors in brain extracts. The antifeedant activity of brain extracts was tested in vivo by injecting the extract and measuring the carotenoids contained in the gut from carrot ingested after the treatment. By HPLC fractionation and tracking the biological activity with the carrot test, we isolated the sulfakinin EQFDDY(SO 3 H) GHMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 30 publications
2
86
0
Order By: Relevance
“…While not demonstrated directly, the distributions of sulfakinin-like immunoreactivity in many insects, particularly the dipterans, suggests a neuromodulatory role for this peptide family in the CNS (Duve et al, 1994;Davis et al, 1996;Nichols and Lim, 1996;East et al, 1997). Additionally, sulfakinins have been shown to stimulate the release of ␣-amylase from the midgut of both the weevil Rhynchophorus ferrugineus and the moth Opisina arenosella (Nachman et al, 1997;Harshini et al, 2002), and have been shown to be potent inhibitors of food intake in the locust Schistocerca gregaria, the cockroach Blatella germanica and the blowfly Phormia regina (Wei et al, 2000;Maestro et al, 2001;Downer et al, 2007).…”
Section: Sulfakinin Isoforms Appear Highly Conserved Both Within Andmentioning
confidence: 99%
See 3 more Smart Citations
“…While not demonstrated directly, the distributions of sulfakinin-like immunoreactivity in many insects, particularly the dipterans, suggests a neuromodulatory role for this peptide family in the CNS (Duve et al, 1994;Davis et al, 1996;Nichols and Lim, 1996;East et al, 1997). Additionally, sulfakinins have been shown to stimulate the release of ␣-amylase from the midgut of both the weevil Rhynchophorus ferrugineus and the moth Opisina arenosella (Nachman et al, 1997;Harshini et al, 2002), and have been shown to be potent inhibitors of food intake in the locust Schistocerca gregaria, the cockroach Blatella germanica and the blowfly Phormia regina (Wei et al, 2000;Maestro et al, 2001;Downer et al, 2007).…”
Section: Sulfakinin Isoforms Appear Highly Conserved Both Within Andmentioning
confidence: 99%
“…As has been noted by many authors, the sulfakinins share structural similarities to members of the vertebrate cholecystokinin (CCK)/gastrin family of peptides (Table·1), as well as to cionin (Table·1), a disulfated peptide isolated from the protochordate tunicate Ciona intestinalis (Johnsen and Rehfeld, 1990). It is the belief of many that these structural similarities are the result of a common ancestry for the two groups of peptides (Nachman et al, 1986a;Nachman et al, 1986b;Nichols et al, 1988;Veenstra, 1989;Schoofs et al, 1990;Maestro et al, 2001;Torfs et al, 2001;Nachman et al, 2005). In addition to the observed sequence homologies, the hypothesis of a common ancestor for the CCK/gastrins and the sulfakinins is supported by the findings that both share a number of conserved functions: both groups are myoactive on the gut, induce the release of the enzyme amylase from the digestive system, and serve as satiety factors (Nachman et al, 1997;Wei et al, 2000;Maestro et al, 2001;Harashini et al, 2002;Downer et al, 2007).…”
Section: Do the Invertebrate Sulfakinins And The Vertebratementioning
confidence: 99%
See 2 more Smart Citations
“…83) They stimulate hindgut contraction in the cockroach, L. maderae, a amylase secretion in the midgut of the weevil, Rhynchophorus ferrugineus, 84) have a cardioacceleratory effect on Periplaneta, and reduced food intake in Schistocerca gregaria and Blatella germanica. 85) The Drosophila sulfakinin gene encodes a 128 amino-acid long protein processed into two GHMRFamide peptides (DSK I and II) and a peptide of unrelated sequence, DSK 0. 79) FLRFamides (also known as myosuppressins), are decapeptides with pleiotropic effects acting on a wide variety of organs.…”
Section: Fmrfamides and Fmrfamide-related Peptides (Farps)mentioning
confidence: 99%